Tertiary Lymphoid Structure-B Cells Narrow Regulatory T Cells Impact in Lung Cancer Patients - Germain, Claire; Devi-Marulkar, Priyanka; Knockaert, Samantha; Biton, Jérôme; Kaplon, Hélène; Letaïef, Laïla; Goc, Jérémy; Seguin-Givelet, Agathe; Gossot, Dominique; Girard, Nicolas; Validire, Pierre; Lefèvre, Marine; et al. (Frontiers in Immunology, 2021)
The abstract is not currently available, please wait for the final typeset article to be published